112k views
4 votes
What are the first four terms of the sequence represented by the expression n(n-2)-3

2 Answers

4 votes

a_n=n(n-2)-3 \\ \\ a_1=1(1-2)-3=1 * (-1)-3=-1-3=-4 \\ a_2=2(2-2)-3=2 * 0-3=0-3=-3 \\ a_3=3(3-2)-3= 3 * 1-3=3-3=0 \\ a_4=4(4-2)-3=4 * 2 -3 =8-3 =5

The first four terms are -4, -3, 0, 5.
User Bethesdaboys
by
7.0k points
6 votes

Answer:

As per the statement:

Given a sequence:


a_n = n(n-2)-3

where, n is the number of terms;

We have to find the first four terms of this sequence:

For n =1


a_1 = 1(1-2)-3 =1(-1)-3 = -1-3 = -4


a_1 = -4

For n =2


a_2= 2(2-2)-3 =2(0)-3 = 0-3 = -3


a_2 = -3

For n =3


a_3 = 3(3-2)-3 =3(1)-3 = 3-3 = 0


a_3= 0

For n =4


a_4 = 4(4-2)-3 =4(2)-3 = 8-3 = 5


a_4= 5

Therefore, the first four terms of the sequence are:

-4, -3, 0 , 5

User WooiKent Lee
by
6.6k points